Using constructions to measure developmental language complexity - Nelson Robert (Cognitive Linguistics)
Models used to explain phenomena are necessarily finer grained than the models used to measure them. In language study, the measures used to assess development (e.g., readability indices) rely on models of language that are too coarse grained to be interpreted in a linguistic framework and so do not participate in linguistic accounts of development. This study argues that the constructionist approaches provide a framework for the development of a practical and interpretable measure of developmental complexity because these approaches feature affordances from which a measurement model may be derived: they describe language knowledge as a comprehensive network of enumerable entities that do not require the imputation of external processes, are extensible to early child language, and hold that the drivers of language development are the learning and generalization of constructions. It is argued here that treating schematic constructions as the unit of language knowledge supports a complexity measure that can reflect developmental changes arising from the learning and productive generalization of these units.